After the reform era, forest management approaches tend to change from state-based to community-based. Arising awareness about the importance of involving communities in forest management, it will not succed without support from the community. Since 2001, Perhutani has implemented a partnership program in the form of CBFM (Joint Forest Management Society), designed to accommodate the dynamic and needs of the community. This paper aims to study the perception of society, equality of status of - Mukhlas Ansori; Endriatmo Soetarto; Dudung Darusman; Leti Sundawati (Forum Pasca Sarjana, 2011)
After the reform era, forest management approaches tend to change from state-based to community-based.  Arising awareness about the importance of involving communities in forest management, it will not succed without support from the community.  Since 2001, Perhutani has implemented a partnership program in the form of CBFM (Joint Forest Management Society), designed to accommodate the dynamic and needs of the community.  This paper aims to study the perception of society, equality of status of the community, and to formulate alternative forestry policy.  This research was quantitative and qualitative research. Sample were taken purposively.  Research location in Perhutani office (BKPH) of Parung Panjang, KPH Bogor.  Public perceptions of CBFM are positive and able to increase revenue, income, absorb labour, and grow productive business. Biophysical condition are better with the following: the fire and illegal logging are reduced, and the rehabilitation of forest is better.  However, it is difficult for the community to get water since Acacia mangium were planted.  The level of community participation in planning and evaluation is low but high in the implementation.  The pattern of partnership is asymmetrical because the decision-making is dominated by Perhutani officers.  In the cooperative agreement, there are many inequalities positions.  CBFM is derivative of developmentalist ideology contrary to the principles of community empowerment.  The partnership is focused more on corporate interests, and is used as reducer of conflict.  Policy scenarios of CBFM are institutional strengthening, acces to forest resources, equality in forest management partnership, and productive business.   Key words: community forestry, partnership, equality, institutional